Parent–child cooking meal together may relate to parental concerns about the diets of their toddlers and preschoolers: a cross-sectional analysis in Japan - Ishikawa, Midori (Nutr J, 2019)
BACKGROUND: Parents often have concerns about the food habits of their young children. Cooking is a frequent behavior related to dietary activities at home. We hypothesized that “a parent cooking meals together with young children might alleviate dietary concerns.” The aim of this study was to identify the relationship between parental cooking practices (e.g., cooking meals together with the child) and diet-related concerns. METHODS: Data were extracted from the “National nutrition survey on preschool children” conducted among nation-wide households with toddlers and preschoolers in 2015 by the Ministry of Health, Labour and Welfare of Japan. Parents were classified into two groups comprising those who cooked meals together with their children and those who did not. The following variables were compared: taking too much time to eat (slow eaters), “picky” eating (eating only certain foods), inconsistent food intake (eating too much or too little), playing with food/utensils while eating, preferring sweetened beverages and snacks over meals, eating too fast to chew well, not swallowing food, disinterested in eating, and spitting out food. The associations between parent–child cooking meals together and the concerns pertaining to the child’s dietary habits and food intake were analyzed and compared between the two groups. RESULTS: The concerns of “picky eating” and “playing with food/utensils while eating” were lower, while “eating too much” was higher in the parent-cooking together group. The intake frequency of fish, soybeans/soy products, vegetables, and milk among children were higher in the “cooking together” group than among those in the “not cooking together” group. Children in the “cooking together” group consumed a significantly greater variety of foods than those in the “not cooking together” group. CONCLUSIONS: Cooking a meal together with a child may be related to the parent’s lower concerns about the dietary habits of the child, including “picky eating” and “playing with food/utensils while eating,” but may also be related to the higher concerns of “eating too much.” ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12937-019-0480-0) contains supplementary material, which is available to authorized users.